Analysis of The Implementation of UEFA Financial Fair Play: A Case Study on Arsenal and Machester United Football Club - Sendy Sendy; Gatot Soepriyanto; Nuraini Sari (Bina Nusantara University, 2014)
This study aims to analyze the implementation of UEFA Financial Fair Play (FFP) to European football clubs. Research is conducted based on Arsenal and Manchester United football clubs financial statements for 2010-2012. The study uses financial simulation to test whether the two England-based club are able to meet the UEFA FFP rules. Analyses were also conducted on the financial performance ratios of both clubs and their effects on the implementation of the UEFA FFP. The result is the two clubs can meet the standard provisions for the implementation of UEFA FFP. In the assessment of financial performance, Arsenal have a slightly better financial ratios than Manchester United. Performance aspects of profitability and solvency became an issue in the implementation of UEFA's FFP, related with debt holdings and high salaries that owned by both clubs.